Pranie pieniędzy na rynku dzieł sztuki — skala zjawiska oraz możliwości przeciwdziałania - Pływaczewski, Wiesław (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The author describes the international art market, highlighting phenomena that are likely to undermine its credibility. These include certain forms of crime, such as forgery, theft, destruction and smuggling of works of art. Above all, however, the article focuses on newly defined forms of cri¬minal activity. Among them are “white collar” crimes, illegal transfers in connection with art bank-ing and money laundering. The author focuses on the latter. His analysis of the problem can also be seen in a historic dimension as underlined in the study. The article ends with some significant in terms of crime prevention findings and observations. They relate to the fight against money laundering involving works of art, the fight seen from the perspective of the international cooperation of law enforcement agencies.
Keywords: pranie pieniędzy; pranie pieniędzy na rynku dzieł sztuki; przeciwdziałanie; rynek dzieł sztuki